Student Academic Competence Questionnaire - O.P. Merkulova (Moscow State University of Psychology and Education, 2024)
The results of the development and standardization of an academic competence questionnaire are presented. The method is based on the understanding of academic competence as a complex of independently developed personal qualities, abilities and skills that ensure the success of educational activities in conditions of its variability during higher education. The theoretical model includes 6 structural and content components (academic motivation, self-organization of educational activities, emotional self-regulation, skills and abilities to work with information, proficiency in oral and written language, communication skills), presented at 3 levels of generality and freedom of transformation (reproductive, reflective, functional). Based on the results of Study 1 (N=199), the preliminary version of the questionnaire was reduced from 144 to 69 items. Comparing the results of successful and unsuccessful students confirmed predictive validity. External criterion validity using the contrast group method is based on comparison of groups of undergraduate and graduate students, correlations with self-organization and academic motivation questionnaires (AMS). Study 2 (N=355) demonstrated a relatively acceptable fit of the data to the theoretical model based on confirmatory factor analysis, consistency with educational experience questionnaire scales. The internal consistency of the scales was confirmed by Cronbach's alpha indicators based on data from studies 1 and 2. Descriptive statistics for Study 2 are provided. Standardization is proposed based on percentile values, because the distributions of values for most scales differ significantly from normal.